Significance of LRFN4 in prognosis and tumor microenvironment of lung adenocarcinoma - Wang, Nana; Cao, Shuming; Tan, Xiaofeng; Liu, Meirong (Frontiers in Pharmacology, 2025)
BackgroundLRFN4 is expressed in various tumors and leukemia cell lines. This study aims to explore the effect of LRFN4 in lung adenocarcinoma (LUAD).MethodsThe data on LUAD patients were collected from the Cancer Genome Atlas and Gene Expression Omnibus database. The expression of LRFN4 in LUAD and LUAD cell lines was analyzed via differential gene analysis, qRT-PCR assay, and Western blotting assay. The correlation of LRFN4 expression with the onset of LUAD were calculated using Pearson correlation analysis. The transcription factors correlated with LRFN4 expression were screened by differential expression analysis and Pearson correlation analysis. Moreover, the effect of LRFN4 on the immune landscape of LUAD was analyzed using CIBERSORT algorithm. The GDSC and CTRP databases were used to analyze the drug sensitivity of hub gene.ResultsLRFN4 was highly expressed in LUAD patients and cells, and LRFN4 expression was correlated with metastasis, pathological stages, and age of LUAD patients. The transcription factors E2F1 and E2F3 could regulate LRFN4 expression by binding upstream of LRFN4. The 8 immune cell infiltration levels were differential between LRFN4high and LRFN4low patients. The ESTIMATEScore and ImmuneScore levels were decreased, the TumorPurity level was elevated, and 6 immune checkpoint expressions were increased in LRFN4high patients. Moreover, LRFN4high patients had inferior prognosis. The mutation rate of TP53, TTN, and MUC6 and the level of TMB were increased in LRFN4high patients. The expressions of TCF3, E2F1, E2F3, and LRFN4 were correlated with the IC50 of multiple drugs.ConclusionLRFN4 may serve as a novel prognostic biomarker for LUAD, shows specific overexpression in LUAD and may be a potential therapeutic target for LUAD patients.